Mesenchymal stromal cells prevent progression of liver fibrosis in a novel zebrafish embryo model - van der Helm, Danny (Sci Rep, 2018)
Chronic liver damage leads to the onset of fibrogenesis. Rodent models for liver fibrosis have been widely used, but are less suitable for screening purposes. Therefore the aim of our study was to design a novel model for liver fibrosis in zebrafish embryos, suitable for high throughput screening. Furthermore, we evaluated the efficacy of mesenchymal stromal cells (MSCs) to inhibit the fibrotic process and thereby the applicability of this model to evaluate therapeutic responses. Zebrafish embryos were exposed to TAA or CCL4 and mRNA levels of fibrosis-related genes (Collagen-1α1, Hand-2, and Acta-2) and tissue damage-related genes (TGF-β and SDF-1a, SDF-1b) were determined, while Sirius-red staining was used to estimate collagen deposition. Three days after start of TAA exposure, MSCs were injected after which the fibrotic response was determined. In contrast to CCL4, TAA resulted in an upregulation of the fibrosis-related genes, increased extracellular matrix deposition and decreased liver sizes suggesting the onset of fibrosis. The applicability of this model to evaluate therapeutic responses was shown by local treatment with MSCs which resulted in decreased expression of the fibrosis-related RNA markers. In conclusion, TAA induces liver fibrosis in zebrafish embryos, thereby providing a promising model for future mechanistic and therapeutic studies.